Peran Brand Credibility Sebagai Mediasi Pengaruh Strategi Celebrity Endorsement Terhadap Brand Equity - Deandra Vidyanata (Universitas Airlangga, 2019)
The celebrity endorsement strategy is considered as one of the promotional tools attract consumers. However, the effectiveness of these strategies in forming brand equity is still questionable. This study aims to examine the effect of the celebrity endorsement strategy on brand equity of endorsed brands. This study uses brand credibility as a mediating variable because endorser credibility is expected to be transferred to brands that will influence the formation of brand equity. The object of research used in this study is OPPO smartphone consumers, that have been increased significantly within the past 4 years. In addition, it is known that many OPPO brands endorse celebrities to introduce their products. The results of this study indicate that the use of celebrity endorsers is not directly able to form brand equity, but the use of celebrity endorsers causes the formation of brand credibility which is ultimately able to form brand equity.